The characterization and quantification of the induced mesophases of poly-l-lactic acid. (4th June 2021) - Baptista, Cameron; Azagury, Aharon; Baker, Christopher M.; Mathiowitz, Edith
Abstract: The pressure-temperature induced mesophases of poly-l -lactic acid (PLA) were studied upon processing at 20, 000 lbf, for 15 min, at varying temperatures from 40 to 120 °C. The morphology and melting behavior of the processed samples were analyzed by x-ray diffraction (XRD), polarized light microscopy (PLM), and differential scanning calorimetry (DSC). Samples processed near and below the glass transition temperature at 52 °C and 63 °C displayed a nematic-like mesophase, characterized by orientational order of the amorphous XRD scattering, birefringence by PLM, and a post-Tg endotherm by DSC. The nematic-like mesophase quantity in these samples was determined to be 8.7%–20.5%, respectively, based on hot-stage XRD and peak deconvolution. This nematic-like state was shown to disorder upon heating around the glass transition at 65 °C. Samples processing above the glass transition temperature at 74 °C, 85 °C, and 120 °C, displayed a condis crystal-like mesophase, characterized by crystalline reflections of the mesophase XRD scattering, birefringence by PLM, and an increased melting endotherm by DSC. The total quantity of mesophase in these samples was shown to be betweeen 8.8% and 15.8%. Thus, this paper reports the characterization and quantification of two distinct PLA mesophases upon pressure-temperature processing: a nematic-like mesophase formed at temperatures below the glass transition and a condis crystal-like mesophase formed at temperatures above the glass transition. Graphical abstract: Image 1 Highlights: The morphology and melting behavior of PLA processed at varying pressure-temperature conditions (were studied using PLM, DSC, and XRD. Samples processed near the glass transition at 63 °C displayed morphology indicative of a nematic-like mesophase. Samples processed above the glass transition at 85 °C displayed morphology indicative of condis crystal-like mesophase. Samples processed at 120 °C (above Tm ) displayed typical semi-crystalline morphology, but with increased crystalline content. Based on hot-stage PLM and hot-stage XRD analysis, mesophase formation was suggested to be a precursor to crystallinity upon reheating.